Americans against the city : anti-urbanism in the twentieth century - Conn, Steven (Oxford University Press, 2014)
It is a paradox of American life that we are a highly urbanized nation filled with people deeply ambivalent about urban life. An aversion to urban density and all that it contributes to urban life, and a perception that the city was the place where ""big government"" first took root in America fostered what historian Steven Conn terms the ""anti-urban impulse."" In response, anti-urbanists called for the decentralization of the city, and rejected the role of government in American life in favor of a return to the pioneer virtues of independence and self-sufficiency. In this provocative and swe.